TINDAK PIDANA DAN BENTUK PERLINDUNGAN TERHADAP ANAK - Frederika Bernadeta Ursula Idam Putri; Triasnti Erika Bais; Fransiska Nyoman Supadi; Yustinus Pedo (The Juris, 2023)
Law enforcement against the crimes of sexual abuse and rape is fudamental in a state of law. The handling of sexual crimes against children in the Indonesian criminal law system is regulated in the Criminal Code and other provisions that specifically regulate sexual violence against children. The case of sexual abuse of 6 students committed by the head of an Islamic boarding school (ponpes) in Gunung Kencana sub-district, Lembak, Banten, is suspected of having molested and raped a number of students. In this study the author wants to examine what criminal offenses ensnare the perpetrators of the crime of sexual abuse and the forms of protection provided to child victims of criminal acts. The research used is nomative juridical research, namely through case studies through news and then linked to theories and existing laws and regulations. Criminal actions that can be imposed on MS perpetrators are Article 76D in conjunction with 81 and 76E in conjunction with 82 of the Child Protection Law with a minimum imprisonment of 5 years and a maximum of 15 years and plus one third and the form of protection provided to child victims of sexual violence crimes, namely assistance at every level of court, psychological assistance and education.